PENGUKURAN KINERJA BERBASIS DAMPAK WASTE DALAM KEGIATAN PERAWATAN TOWER TELEKOMUNIKASI - Rein Rante; Agung Sutrisno; Johan S C Neyland (JURNAL POROS TEKNIK MESIN UNSRAT, 2017)
Waste is an activity that absorb or wasting the resource like the expenses or time that added but that’s not adding any value in that activity. The purpose of this study was to identify the correlation between the kind of waste and the performance size in the maintenance activity. To reach the purpose, case study in the maintanence of the tower was studied. From the study that have been done, it obtained various kind of critical waste and the correlation with performance of maintenance. From the result of this study, it obtained the critical waste like the employee that trying to fixed the broken machine with the waste priority number (WPN) of 70.Keywords: Waste. WPN, towe maintenance telecommunication.